Hahnemann and Allergy (Homoeopathy for All, 2026)
In daily practice, one repeatedly  meets patients who seem to react  out of all proportion to the apparent  cause. One patient begins to sneeze  every spring as if the season itself  had become an adversary. Another  develops burning eyes and fluent  coryza from flowers, dust, or slight  atmospheric change. A third breaks  into urticaria after a particular  food, while yet another passes  from recurrent nasal irritation into  tightness of chest and asthmatic  suffering. Modern medicine  commonly gathers many such states  under the word allergy. Yet the  attentive physician soon realizes that  the deeper question is not merely  the external cause, but the peculiar  manner in which the individual  organism receives and answers it.
Keywords: atmospheric change; susceptibility; allergy; prior exposure